Influence of Fly Ash, Bottom Ash, and Light Expanded Clay Aggregate on Concrete - S. Sivakumar; B. Kameshwari (Advances in Materials Science and Engineering)
Invention of new methods in strengthening concrete is under work for decades. Developing countries like India use the extensive reinforced construction works materials such as fly ash and bottom ash and other ingredients in RCC construction. In the construction industry, major attention has been devoted to the use of fly ash and bottom ash as cement and fine aggregate replacements. In addition, light expanded clay aggregate has been introduced instead of coarse aggregate to make concrete have light weight. This paper presents the results of a real-time work carried out to form light weight concrete made with fly ash, bottom ash, and light expanded clay aggregate as mineral admixtures. Experimental investigation on concrete mix M20 is done by replacement of cement with fly ash, fine aggregate with bottom ash, and coarse aggregate with light expanded clay aggregate at the rates of 5%, 10%, 15%, 20%, 25%, 30%, and 35% in each mix and their compressive strength and split tensile strength of concrete were discussed for 7, 28, and 56 days and flexural strength has been discussed for 7, 28, and 56 days depending on the optimum dosage of replacement in compressive strength and split tensile strength of concrete.